Comparative analysis of the variation characteristics of O3, NO2 and CO in the boundary layer in coastal cities and inland cities in the middle latitude regions in China. (December 2018) - Li, Jun; Zhao, Zhonghao
Abstract: Based on the hourly monitoring data of O3 concentration, and its closely related NO2 and CO concentration in four coastal cities (Qingdao, Yantai, Weihai, Rizhao) and four inland cities (Dezhou, Liaocheng, Heze and Jining) in Shandong Province from 2009 to 2017, we compared and analyzed variations of O3, NO2 and CO pollutants in the boundary layer in both coastal and inland cities in mid-latitude regions, and explored their causes. It is found that O3 pollution showed an aggravating tendency in coastal and inland cities from 2012 to 2017, especially remarkably in inland cities. However, NO2 and CO pollution showed an opposite tendency. Seasonal variation of O3 pollution in the boundary layer of coastal cities in the mid-latitude showed an M-shaped bimodal structure, similar to that in low latitude cities, while NO2 and CO show a V-shaped structure with a maximum in winter and a minimum in summer. The diurnal variation of O3 concentration is featured with a high concentration in the daytime and a low one in the night, while NO2 and CO concentration show a bimodal curve with a high concentration both in the morning and evening.